Reshaping consent so we might improve participant choice (II) – helping people decide - Hugh Davies; Rosie Munday; Maeve O’Reilly; Catriona Gilmour Hamilton; Arzhang Ardahan; Simon E Kolstoe; Katie Gillies (Research Ethics Review)
Research consent processes must provide potential participants with the necessary information to help them decide if they wish to join a study. On the Oxford ‘A’ Research Ethics Committee we’ve found that current research proposals mostly provide adequate detail (even if not in an easily comprehensible format), but often fail to support decision making, a view supported by published evidence. In a previous paper, we described how consent might be structured, and here we develop the concept of an Information and Decision Aid (IDA) that can support decision making and be used to guide the dialogue between researcher and potential participant. Our proposal requires limited changes to current processes or paperwork and would provide an easily accessible document for others that the potential participant might approach for advice. It could later be integrated with the Informed Consent Form to ensure all matters of concern to the individual participant have been addressed before consent is formally signed off.